1994
DOI: 10.1152/ajplung.1994.267.2.l120
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of hypoxic vasoconstriction in the canine isolated pulmonary artery: role of endothelium and sodium pump

Abstract: Contraction of canine pulmonary artery to hypoxia in vitro is both endothelium dependent and independent. The mechanisms which underlie this phenomenon were studied. Rings of canine pulmonary artery were suspended for isometric force recording in tissue baths containing modified Krebs-Ringer bicarbonate solution. Tissues were first contracted with norepinephrine [effective dose at 35% (ED35) concentration]. Subsequent exposure to hypoxia induced a triphasic response: an initial phasic transient contraction (ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 0 publications
5
29
0
Order By: Relevance
“…This is in agreement with other reports that the full expression of sustained HPV requires an intact endothelium (10,13,18), although this is not a universal finding (4,16). We have also reported that the generation of tension during phase II appears to involve Ca 2ϩ sensitization of the contractile apparatus, which is protein kinase C independent (24) and which appears to involve activation of Rho kinase (25).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with other reports that the full expression of sustained HPV requires an intact endothelium (10,13,18), although this is not a universal finding (4,16). We have also reported that the generation of tension during phase II appears to involve Ca 2ϩ sensitization of the contractile apparatus, which is protein kinase C independent (24) and which appears to involve activation of Rho kinase (25).…”
supporting
confidence: 92%
“…In agreement with our earlier observations (22), we found that, whereas phase I was endothelium independent, phase II was completely dependent on the presence of an intact endothelium. Analogous biphasic responses to hypoxia have been described in a number of pulmonary vascular preparations, and a similar endothelium dependency of the full generation of sustained HPV has also been observed (10,13,18), although it is noted that this finding is not universal (4,16).…”
Section: Discussionsupporting
confidence: 54%
“…This possibility is made unlikely by the lack of effect of TRAM34, UCL1684, iberiotoxin (17), ouabain (inhibitor of Na ϩ /K ϩ -ATPase; Ref. 27) and BaCl 2 (17). Alternatively, the activation of SERCA by NO is also cyclic GMP independent (1).…”
Section: Discussionmentioning
confidence: 99%
“…1). Whereas the phase 1 constriction is relatively unaffected by removal of the endothelium, in most reports phase 2 is abolished (Hoshino, Morrison & Vanhoutte, 1994;Leach et al 1994;Zhang & Morice, 1994). It is notable that a biphasic response of similar time course has also been observed in some salt-perfused lung preparations (Robertson, Clapham & Ward, 1994).…”
Section: Introductionmentioning
confidence: 98%